Climate change and the threat of disaster: the moral case for taking out insurance at our grandchildren's expense - Rendall, Matthew (Wiley-Blackwell, 2011)
Is drastic action against global warming essential to avoid impoverishing our descendants? Or does it mean robbing the poor to give to the rich? Alas, we don’t yet know. Yet most of us can agree on the importance of minimizing expected deprivation. Because of the vast number of future generations, if there is any significant risk of catastrophe, this implies drastic and expensive carbon abatement unless we discount the future. I argue that we should not discount. Instead, the rich countries should stump up the funds to support abatement both for themselves and the poor states of the world.